PENGARUH KESADARAN, PENGETAHUAN DAN PEMAHAMAN, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Intan Ellya Maesyarah; Jacobus Widiatmoko; M.G. Kentris Indarti (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to obtain empirical evidence of the influence of taxpayer awareness, taxpayer knowledge and understanding, service quality, and tax sanctions on individual taxpayer compliance. This research sample used a purposive sampling technique of 100 individual taxpayer respondents registered at KPP Pratama Pati with certain criteria and analyzed using multiple linear regression analysis with the help of the IBM Statistics SPSS 26 application. The data used in this research is primary data by means of distribution. to respondents. The research results show that taxpayer knowledge and understanding, service quality, and tax sanctions have a significant effect on taxpayer compliance, while taxpayer awareness has no effect on taxpayer compliance.